Analisis Sitasi Tik Ilmeu: Jurnal Ilmu Perpustakaan dan Informasi IAIN Curup Tahun 2020–2025 (Sebuah Kajian Bibliometrika) - Andi Ayu fadnur Irsan; Ahmad Aryadi (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2026)
This study aims to map the publication dynamics, referencing patterns, and scientific landscape defining Tik Ilmeu: Jurnal Ilmu Perpustakaan dan Informasi IAIN Curup during the 2020 to 2025 period, employing a descriptive bibliometric method by analyzing 136 articles which generated a total of 2,611 references. The results indicate that the journal experienced significant volume growth, peaking at 31 articles in 2023, confirming improved visibility and operational stability. Analysis of reference types reveals a high scientific standard, evidenced by the dominance of Articles or Journals (60.51%) as the primary citation source, while Books maintain a solid theoretical foundation. The most influential authors are Sugiyono (41 citations) and Sulistyo-Basuki (38 citations), pointing to the dominance of methodological and foundational theoretical references commonly used in final paper writing, strengthened by citation circulation among other PTKI academics. Furthermore, the journal’s research focus shows a strategic balance between Literacy, Reading Culture, and Community Empowerment (35.7%) and Technology, Automation, and Information Digitization (22.2%) topics. It is concluded that Tik Ilmeu is a rapidly growing journal with sound scientific referencing standards, serving as a vital platform for the development of Islamic Library and Information Science research that is both socio-educatively oriented and responsive to technological advancements.